2016
DOI: 10.1681/asn.2016050510
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin Binds Specifically to Sodium-Glucose Cotransporter 2 in the Proximal Renal Tubule

Abstract: Kidneys contribute to glucose homeostasis by reabsorbing filtered glucose in the proximal tubules via sodium-glucose cotransporters (SGLTs). Reabsorption is primarily handled by SGLT2, and SGLT2-specific inhibitors, including dapagliflozin, canagliflozin, and empagliflozin, increase glucose excretion and lower blood glucose levels. To resolve unanswered questions about these inhibitors, we developed a novel approach to map the distribution of functional SGLT2 proteins in rodents using positron emission tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 28 publications
0
54
1
Order By: Relevance
“…357 Studies using radio-fluorinated labeling of dapagliflozin have also examined organ specific SGLT2inhibitor binding in rat tissues, and while skeletal binding was not assessed, no specific binding to skeletal muscle was observed. 358 Similarly, mRNA expression of SGLT1 in muscle tissue of control and diabetic rats was found to be negligible. 359 Taken together, these studies indicate that SGLT2-inhibitor drugs are unlikely to have a specific direct effect on musculoskeletal tissues at the cellular level.…”
Section: Skeletal Effects: Clinical Investigation and Fracture Riskmentioning
confidence: 94%
See 1 more Smart Citation
“…357 Studies using radio-fluorinated labeling of dapagliflozin have also examined organ specific SGLT2inhibitor binding in rat tissues, and while skeletal binding was not assessed, no specific binding to skeletal muscle was observed. 358 Similarly, mRNA expression of SGLT1 in muscle tissue of control and diabetic rats was found to be negligible. 359 Taken together, these studies indicate that SGLT2-inhibitor drugs are unlikely to have a specific direct effect on musculoskeletal tissues at the cellular level.…”
Section: Skeletal Effects: Clinical Investigation and Fracture Riskmentioning
confidence: 94%
“…SGLT2 expression was not detected in cells of either the osteoblast or osteoclast lineages; SGLT1 was detected in MC3T3‐E1 differentiating osteoblasts, albeit at levels <1% of that observed in the kidney, but not in any cells of osteoclast lineage . Studies using radio‐fluorinated labeling of dapagliflozin have also examined organ specific SGLT2‐inhibitor binding in rat tissues, and while skeletal binding was not assessed, no specific binding to skeletal muscle was observed . Similarly, mRNA expression of SGLT1 in muscle tissue of control and diabetic rats was found to be negligible .…”
Section: Drugs and Bonementioning
confidence: 99%
“…For example, using microPET to monitor Me-4FDG excretion into the urinary bladder, we have shown that intravenous injection of phlorizin or the specific SGLT2 inhibitor dapagliflozin rapidly increases excretion of Me-4FDG into the urinary bladder (Fig. 5 a) [ 32 ]. Dapagliflozin acts specifically on the kidneys, as shown by microPET imaging of mice injected with 4-[ 18 F]fluoro-dapagliflozin (F-Dapa) [ 32 ].…”
Section: Inhibition Of Glucose Reabsorptionmentioning
confidence: 99%
“…D apagliflozin is a selective and competitive inhibitor of the renal proximal tubule sodium-glucose-linked transporter 2 (SGLT2). [1][2][3][4] It is approved for the treatment of type 2 diabetes mellitus (T2DM), where it promotes glycosuria. 1,5 T2DM increases the incidence of congestive heart failure (CHF).…”
mentioning
confidence: 99%